Plantæ vasculares in Lapponia orientali sponte nascentes - Fellman, Nils Isak. (Helsingfors : J. Simelii, 1882)
In: Notiser ur Sällskapets pro Fauna et Flora Fennica förhandlingar. 1882. i-lxx, 1-99. Reprint of Fellman's work published 1864-1869. Mode of access: Internet.